Predicting the development of crescentic bed patterns: a comparison of linear stability model results with field observations - Tiessen, Meinard (2010)
Large scale patterns in the seabed often occur in the nearshore zone of sandy beaches. A widely occurring bed pattern is the crescentic bar. These bed patterns develop under moderate wave conditions, and form a lunate shaped alongshore pattern in front of a coast. Over recent years, knowledge concerning the development, occurrence, and characteristics of these bed patterns has been significantly expanded through field studies and modelling attempts. An example of such a model is the linear stability analysis, which describes the initial development of crescentic bed patterns along an undisturbed beach.